Canva's efficacy in improving student writing skills - Dwi Nirmala, Lulia; Sabat, Yuliyanto (Fakultas Ilmu Pendidikan Universitas PGRI Kanjuruhan Malang, 2023)
More and more studies on language education are currently considering the use of technology in writing training. Furthermore, the importance of using visual media in EFL lessons has been highlighted by the current study, which aims to help students improve their writing skills. The current study aims to investigate the impact of Canva on students' writing skills. This was accomplished by randomly assigning forty-four Indonesian EFL students—known as the experimental and control groups—to two writing classes. Prior to starting treatment, both groups completed a pre-test. Throughout the sessions, the Communicative Language Teaching (CLT) approach was used to instruct both classes. To help them explore their writing ideas, students in the experimental group were instructed to utilize Canva as a writing medium. After the treatment, a post-test was administered to both groups. The results of the pre-test and post-test were then processed using SPSS with the t test. The results of this test showed that the experimental group that was given treatment got better scores than the control group. After that, interviews were carried out to obtain qualitative data. As a result, each student had positive and negative perceptions.